THE IMPACT OF MONETARY AND FISCAL POLICY ON UZBEKISTAN'S EXPORT VOLUME: AN EMPIRICAL ANALYSIS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In recent decades, the role of exports in Uzbekistan's economy has significantly increased. The country remains an important exporter of cotton, gold, and uranium, and in recent years has expanded to include textiles, food products, and services. On the path to trade development, the government’s economic policy—particularly in the monetary and fiscal spheres—plays a key role